Frequency support characteristics of grid‐interactive power converters based on the synchronous power controller. Issue 4 (31st January 2017) - Zhang, Weiyi; Remon, Daniel; Rodriguez, Pedro
Abstract : Grid‐interactive converters with primary frequency control and inertia emulation have emerged and are promising for future renewable generation plants because of the contribution in power system stabilisation. This study gives a synchronous active power control solution for grid‐interactive converters, as a way to emulate synchronous generators for inerita characteristics and load sharing. As design considerations, the virtual angle stability and transient response are both analysed, and the detailed implementation structure is also given without entailing any difficulty in practice. The analytical and experimental validation of frequency support characteristics differentiates the work from other publications on generator emulation control. The 10 kW simulation and experimental frequency sweep tests on a regenerative source test bed present good performance of the proposed control in showing inertia and droop characteristics, as well as the controllable transient response.